2002
DOI: 10.1016/s0014-5793(02)02535-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal glycosylation and altered Golgi structure in colorectal cancer: dependence on intra‐Golgi pH

Abstract: Abnormal glycosylation of cellular glycoconjugates is a common phenotypic change in many human tumors. Here, we explore the possibility that an altered Golgi pH may also be responsible for these cancer-associated glycosylation abnormalities. We show that a mere dissipation of the acidic Golgi pH results both in increased expression of some cancer-associated carbohydrate antigens and in structural disorganization of the Golgi apparatus in otherwise normally glycosylating cells. pH dependence of these alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 50 publications
9
122
0
Order By: Relevance
“…Actin depolymerization may impair this functional coupling and generate an inappropriate gradient formation (and intra-Golgi pH), which at ultrastructural level would initially lead to cisternae swelling and then to their collapse. Abnormal ion gradients and pH coupled to the loss of actin cytoskeleton integrity in the Golgi complex could impair both protein transport-and non-transport-associated functions (for instance, protein and lipid glycosylation) [Axelsson et al, 2001;Kellokumpu et al, 2002]. In line with this hypothesis, interference with either the activity of (V)H þ -ATPase [Yilla et al, 1993] or with actin polymerization [Hirschberg et al, 1998;Jacob et al, 2003;Cobbold et al, 2004] results in an altered post-Golgi transport.…”
Section: Discussionmentioning
confidence: 99%
“…Actin depolymerization may impair this functional coupling and generate an inappropriate gradient formation (and intra-Golgi pH), which at ultrastructural level would initially lead to cisternae swelling and then to their collapse. Abnormal ion gradients and pH coupled to the loss of actin cytoskeleton integrity in the Golgi complex could impair both protein transport-and non-transport-associated functions (for instance, protein and lipid glycosylation) [Axelsson et al, 2001;Kellokumpu et al, 2002]. In line with this hypothesis, interference with either the activity of (V)H þ -ATPase [Yilla et al, 1993] or with actin polymerization [Hirschberg et al, 1998;Jacob et al, 2003;Cobbold et al, 2004] results in an altered post-Golgi transport.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we examined the effect of JNK inhibition in MCF7 cells, which is a tumour cell line known to have a fragmented Golgi (Kellokumpu et al, 2002) and that requires JNK signalling for its proliferation (Mingo-Sion et al, 2004), as confirmed by their higher JNK activity compared to HeLa cells (supplementary material Fig. S2A).…”
Section: Inhibition Of the Jnk Pathway Blocks Cleavage Of The Golgi Rmentioning
confidence: 99%
“…A variety of tumor cell types exhibit Golgi complexes that are fragmented and dispersed by an unknown mechanism (16). Cultured cells from different human pancreatic epithelial tumor cell lines (HPAF-II, BxPC-3) were stained for a Golgi marker that was detected by immunofluorescence.…”
Section: Modulation Of Src Activity Affects Golgi Compartment Integrimentioning
confidence: 99%